Peran Perpustakaan dalam Menumbuhkan Sikap Pancasilaisme Bangsa Indonesia - Suprapto Suprapto (IJAL (Indonesian Journal of Academic Librarianship), 2018)
Pancasila as the foundation of Indonesian’ national philosophy has been variously interpreted and sometimes even manipulated by political actors and society who take refuge behind the legitimacy of the Pancasila as national ideology. The transition from the New Order era to the Reformation era has had an impact as a result of the Reformation movement by giving rise to various views that sometimes weaken the role of the Pancasila ideology and can threaten the unity of the Indonesia. Pancasila as a subject needs to be properly taught to the citizens. Teaching Pancasila as a part of citizenship education can be started from an early age so that all citizens would behave and live according to its values. The library as a means of providing information has an important role in supporting lifelong education, including providing and disseminating resources about Pancasila.